Accidental Gravity : Residents, Travelers, and the Landscape of Memory - Quetchenbach, Bernard W., 1955- (Book collections on Project MUSE., 2017)
"The compelling essays in Bernard Quetchenbach's Accidental Gravity move from upstate New York to the western United States, from urban and suburban places to wild lands. In the first section of the book, he focuses on suburban neighborhoods, where residents respond ambivalently to golf-course geese and other unruly natural presences; in the second section, he juxtaposes these humanized places with Yellowstone National Park. Quetchenbach writes about current environmental issues in the Greater Yellowstone area--wildfire, invasive species, ever-increasing numbers of tourists--in the context of climate change and other contemporary pressures. Accidental Gravity negotiates the difficult edge between a naive belief in an enduring, unassailable natural world and the equally naive belief that human life takes place in some unnatural, more mediated context. The title refers to the accidental but nonetheless meaningful nexus where the personal meets and combines with the universal--those serendipitous moments when the individual life connects to the larger rhythms of time and planet"--